Acute ischaemic heart block in hypoplastic left heart syndrome. (22nd December 2014) - Burkett, Dale A.; Wilson, Neil; Mitchell, Max B.; Younoszai, Adel K.
Abstract: In hypoplastic left heart syndrome, thrombosis of the native ascending aorta is rare and often fatal; there are no previously reported cases presenting with acute heart block. We review a case of native ascending aorta thrombosis in a 2-year-old boy with hypoplastic left heart syndrome, presenting with acute heart block. This case highlights the benefit of multi-modality imaging in complex cases.